Penempatan Kapasitor Shunt Pada Sistem Kelistrikan 150 Kv Sulselrabar - Muhammad Ruswandi Djalal; Herman Herman (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Power flow study is the determination or calculation of the voltage, current and power factor or reactive power that is present at various points in a power grid in the normal state, whether current or expected to occur in the future. From the result of normal condition analysis, it is obtained the critical voltage profile on bus 31 tonasa and used as the candidate for mounting capacitor. From the calculation results obtained capacities installed 16.0413 Mvar. From the simulation results before the installation and after installation of the capacitor visible improvement of voltage profile and channel losses. The channel losses prior to installation are 32,649 MW and after installation of 31,834 MW. For voltage profiles, some buses also look better, than before in critical conditions to be marginal. On the previous bus tonasa 0.933 pu to 0.953043 pu